Coastal Tourism Suitability and Carrying Capacity Index in Pangandaran Beach, West Java Province - Shafira Bilqis Annida; Faqih Baihaqi; Yusfi Sri Wahyunintyas; Riyanti Rahmawati; Kurnia Lucky Fadillah; Selvi Centia (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2025)
Pangandaran West Beach is a popular destination visited by many tourists, both local and international. This study aims to analyze the tourism suitability index and carrying capacity of the West Coast of Pangandaran, West Java, as a beach recreation-based tourist destination. This research was conducted in April 2025. The method used was direct observation to collect primary data on environmental parameters, with 5 stations spaced 636 m apart. Data analysis was conducted using the tourism suitability index and the area's carrying capacity, categorized into three main types: beach recreation, camping, and swimming. The results showed that the tourism suitability index for Pangandaran West Beach in the categories of beach recreation, camping, and swimming tourism was 97.3%, 91.7%, and 85.9%, respectively, and is classified as